Frequency analysis of British versus American English vocabulary in EFL textbooks used in Uzbekistan - Axrorova , Pokiza; Mukhamedova , Nigora Abdulhayevna (The Lingua Spectrum, 2026)
The article analyzes the importance of learning English in Uzbekistan and its role as an international language. A comparative analysis of the English and Uzbek language tenses is conducted, and the main difficulties faced by English as foreign language (EFL) learners are highlighted. The complexity of time and type categories in English, their equivalents in Uzbek, as well as typical mistakes made by students are analyzed using examples. In addition, the possibilities of overcoming these difficulties with the help of effective pedagogical approaches, namely contrastive analysis, visual aids and communicative exercises, are shown. The system of tenses, English as a foreign language, English, Uzbek, comparative analysis, present perfect tense, pedagogical approach, assimilation. Nowadays, English has become the main means of communication, business, education and culture all over the world. The article examines the stages of English language development, problems, proposed solutions and opinions of scientists. The goal is to help students develop the skills necessary to successfully master this language by providing them with the right approaches and techniques in the process of learning English. The article is also supplemented with foreign experience and proposals to improve the quality of English language teaching in Uzbekistan.